The Role of Electronic Banking Services in Improving Profitability in Libyan Commercial Banks." A Field Study on Commercial Banks in the City of Al-Bayda"(National Commercial Bank, Al-Wahda Bank, North Africa Bank). (Al-Mukhtar Journal of Economic Sciences, 2025)
This study aimed to identify the role played by electronic banking services (represented by providing electronic banking services, their usage cost, and the speed of execution) in improving the profitability of Libyan commercial banks. The study sample included three commercial banks: National Commercial Bank, Unity Bank, and North Africa Bank, located in the city of Al-Bayda. To achieve the study’s objective, the researchers used a questionnaire, distributing 50 questionnaires to employees at the banks under study, of which 44 were valid for analysis. The data were analyzed using SPSS, following a descriptive-analytical approach with both documentary and quantitative methods. The study results indicated that electronic banking services play a role in enhancing the level of profitability in Libyan commercial banks. The study recommended that commercial banks work on updating electronic banking applications in accordance with labor market requirements.
Keywords: Electronic Banking Services; Commercial Banks’ Profitability.